The global burden of low back pain attributable high body mass index over the period 1990–2021 and projections up to 2035 - Ye, Jishi; Chen, Jingli; Ding, Huang; Xia, Zhongyuan; Wang, Juan; Jia, Yifan (Frontiers in Nutrition, 2025)
ObjectiveLow back pain (LBP) is a widely disease burden that transcends geographical, cultural, and demographic boundaries, with high body mass index (BMI) recognized as one of its well-established risk factors.MethodsData on LBP attributed to high BMI were retrieved from the Global Burden of Disease (GBD) study 2021 online database. To evaluate the magnitude and direction of the trend in DALYs, a Joinpoint Regression Analysis (JRA) was performed. Additionally, an autoregressive integrated moving average (ARIMA) model was utilized to forecast future trends in DALYs indicators associated with LBP for the subsequent 15 years.ResultsThe impact of high BMI on LBP has shown a progressive increase annually from 1990 to 2021, with a more pronounced disease burden observed in regions with higher economic status. Within areas of comparable economic levels, older age correlates with a heightened burden of disease, and females experience a relatively greater disease burden compared to males. Projections based on the autoregressive integrated moving average (ARIMA) model indicate that the global burden of disease is predicted to continue its upward trajectory over the next 15 years.ConclusionHigher levels of BMI, along with age and gender, are associated with an increased burden of LBP. The global burden of LBP attributable to high BMI is predicted to continue rising over the next 15 years. This study offers additional evidence to support the development and implementation of policies and strategies aimed at preventing and mitigating future increases in the burden of LBP.